Lipoma-like Pleomorphic Adenoma of the Trachea - Eom, Jung Seop; Lee, Chang Hun; Kim, Ah Rong; Lee, So Jung; Jung, Se Jin (Archives of Clinical and Medical Case Reports, 2020)
Endotracheal pleomorphic adenoma is an extremely rare disease. A 67-year-old Korean woman, who had complained of progressive dyspnea and wheezing presented with an endotracheal mass in the upper trachea on a chest CT scan. The tumor was removed by rigid bronchoscopy with diode laser ablation at the base. From histologic examination, the mass consisted of extensive mature fat tissue (about 80% of tumor volume) and strips of usual pleomorphic adenoma with diverse histology. Nuclear atypia or mitotic activity of epithelial cells was not identified. Therefore, it was diagnosed as lipoma-like pleomorphic adenoma. Lipoma-like pleomorphic adenoma arising in the trachea is an extremely rare condition. To the best of our knowledge, this is the first such trachea case reported in the English literature.